The relations between Church and state in the Argentine Republic - Navarro Floria, Juan G. (European journal for church and state research, 2002)
Abstract der Zeitschrift: The author discusses the relation between the Catholic Church and the Argentinian State during the recent and past centuries. He does it with special reference to recent legislation